FREQUENCY AND CONSEQUENCES OF FUNCTIONAL LIMITATIONSIN KNEE OSTEOARTHRITIS PATIENTS BELOW 50 YEARS OF AGE - Fakhira Arain (Baqai Journal of Health Sciences)
Objective: Measure and quantify the extent of functional limitations in knee osteoarthritis patients under 50. This could include a range of motion, mobility, and activities of daily living (ADLs). Method: This observational study was conducted at the Baqai Institute of Diabetology and Endocrinology (BIDE) in its specialized foot clinic from 2015 to 2016. Data were collected from 80 participants of all genders who were under the age of 50. Individuals with a history of road traffic accidents (RTA), osteomyelitis, tuberculosis of joints, tumors, or those who had undergone ligament surgery were excluded from the study. The collected data were subjected to descriptive analysis using statistical package for social sciences to determine the frequency of various parameters. Result: Participants were 80 (male + female) with an average age of 45.1 years and a standard deviation of 4.2. Regarding pain, the mean score was 6.5 with a standard deviation of 1.2. In terms of pain frequency, 56.3% reported constant pain. About mobility, 70% could walk normally. Of the participants, 25% had a limping gait. For descending stairs, 35% could do so without difficulty. Moreover, nearly all 98.8% experienced discomfort when squatting. Regarding muscle range of motion, active motion was associated with pain in flexion 35%, extension 7.5%, and both flexion and extension 47.5%. These unexpected results suggest a higher level of impairment than anticipated. Conclusion: Our study revealed no statistically significant difference in the intensity of stiffness. However, there was a gender difference in the pain and physical function limitations.